Proceedings of the 16th International Symposium on Management (INSYMA 2019) 2019
DOI: 10.2991/insyma-19.2019.7
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting company’s cash holding

Abstract: This study aims to analyze the factors affecting several companies' cash holdings. Some of the factors were net working capital (NWC), cash flow, capital expenditure, leverage, and market-to-book. The samples used in this study were 318 non-financial companies listed in the IDX in 2013-2017. The approach used was a quantitative approach with the linear regression method. The result of the study was that net working capital (NWC), capital expenditure, and leverage had a negative significant effect on cash holdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
2
1
1
Order By: Relevance
“…This research supports the research results of (Amalia et al, 2018;Liadi and Suryanawa, 2018), who found that determining the amount of cash holding is not affected by the company's capital expenditures. This research contrasts with the results of research by (Arfan et al, 2017;Guizani, 2017;Herlambang et al, 2019;Maheshwari and Rao, 2017;Serly and Melandy, 2021;Tayem, 2017), who find high levels of corporate capital expenditure will significantly reduce the amount of cash holding because it is used to finance capital expenditure. The results of this study have a direction that is contrary to the research of (Thu and Khuong, 2018;Trinh and Thuy Mai, 2016), who found that the amount of cash holding will increase as the company's capital expenditure increases.…”
Section: Effect Of Cash Conversion Cycle On Cash Holding the Results ...contrasting
confidence: 91%
See 3 more Smart Citations
“…This research supports the research results of (Amalia et al, 2018;Liadi and Suryanawa, 2018), who found that determining the amount of cash holding is not affected by the company's capital expenditures. This research contrasts with the results of research by (Arfan et al, 2017;Guizani, 2017;Herlambang et al, 2019;Maheshwari and Rao, 2017;Serly and Melandy, 2021;Tayem, 2017), who find high levels of corporate capital expenditure will significantly reduce the amount of cash holding because it is used to finance capital expenditure. The results of this study have a direction that is contrary to the research of (Thu and Khuong, 2018;Trinh and Thuy Mai, 2016), who found that the amount of cash holding will increase as the company's capital expenditure increases.…”
Section: Effect Of Cash Conversion Cycle On Cash Holding the Results ...contrasting
confidence: 91%
“…This study obtained results that support the research of (Herlambang et al 2019;Maheshwari and Rao, 2017;Serly and Melandy, 2021;Tayem, 2017), namely the greater the net working capital, the smaller the amount of cash holding. However, this research is not in line with the research of (Astuti et al, 2019;Jebran et al, 2019;Juardi et al, 2021;Liadi and Suryanawa, 2018;Wulandari and Setiawan, 2019) who get an increase in net working capital will increase the amount of cash holding.…”
Section: Effect Of Cash Conversion Cycle On Cash Holding the Results ...supporting
confidence: 85%
See 2 more Smart Citations
“…Perusahaan dengan pengelolaan cash yang baik akan lebih mudah dalam memenuhi biaya operasional hingga biaya tak terduga (Singh & Misra, 2019). Cash holdings menjadi hal penting karena besaran cash yang dimiliki perusahaan menandakan kemampuan perusahaan dalam memenuhi kewajiban (Herlambang et al, 2019).…”
unclassified